Variational Inequalities for Systems of Strongly Nonlinear Elliptic Operators of Infinite Order (Global Journal of Science Frontier Research, 2018)
We are concerned with the existence of weak solutions of strongly nonlinear variational inequalities for systems of infinite order elliptic operators of the form: Ar(u)(x)+ Br(u)(x), Ar(u)(x)+ Br(u)(x),
Keywords: systems of strongly nonlinear elliptic operators of infinite order-variational inequalities